Resin composition, method for producing resin composition, pellet, and molded article
A resin composition with aromatic and aliphatic polyamide resins, carbon black, and a mold release agent addresses weather resistance and water absorption issues in polyamide resin products, enhancing mechanical strength and appearance.
Patent Information
- Application Number
- JP2023112625
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-07
- Publication Date
- 2025-01-20
AI Technical Summary
Polyamide resin-based molded products face issues with poor weather resistance and increased ΔE values after accelerated weathering tests, along with high water absorption rates, especially when reinforcing materials are added, leading to decreased glass transition temperature and visible precipitates.
A resin composition combining aromatic and aliphatic polyamide resins with carbon black, amorphous resin, and a mold release agent, with specific mass ratios and content levels, to enhance mechanical strength and maintain appearance quality.
The resin composition achieves low ΔE values before and after weathering tests, reduced water absorption, and maintains excellent initial appearance, while improving mechanical properties.
Smart Images

Figure 2025009546000001 
Figure 2025009546000002 
Figure 2025009546000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition, a method for producing the resin composition, pellets, and a molded article, and more particularly to a resin composition containing a polyamide resin as a main component. [Background technology]
[0002] Polyamide resin, a representative engineering plastic, is easy to process and has excellent mechanical properties, electrical properties, heat resistance, and other physical and chemical properties, which is why it is widely used in vehicle parts, electrical and electronic equipment parts, and other precision equipment parts. Among such polyamide resins, aromatic polyamide resins, typified by polyamide resins composed of diamine-derived structural units and dicarboxylic acid-derived structural units, in which 70 mol % or more of the diamine-derived structural units are derived from xylylenediamine, have excellent mechanical strength and are therefore widely used in various applications (e.g., Patent Document 1, etc.). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-143023 A Summary of the Invention [Problem to be solved by the invention]
[0004] In recent years, the applications of polyamide resins have expanded, and depending on the application, molded products made from polyamide resins are subject to ΔE * The water absorption rate (%) after the moist heat test is small, and the ΔE * It is required that the initial appearance of the embossed product is excellent and that the surface roughness is small. Here, in order to improve the mechanical strength of molded articles formed from polyamide resins, a reinforcing material is blended. However, blending a reinforcing material tends to deteriorate the weather resistance of the molded articles obtained. When a polyamide resin absorbs water in a moist heat environment, the glass transition temperature of the resin composition decreases, and low molecular weight components of the polyamide and release agents precipitate, which tends to increase ΔE* before and after the moist heat test.
[0005] The present invention aims to solve such problems, and provides a resin composition containing a polyamide resin, a reinforcing material, and a release agent, which has a ΔE * The water absorption rate (%) after the moist heat test is small, and the ΔE * The present invention aims to provide a resin composition capable of providing a molded article having a small grain size and excellent initial appearance as a grain molded product, as well as a method for producing the resin composition, pellets, and a molded article. [Means for solving the problem]
[0006] In view of the above-mentioned problems, the present inventors have conducted research and found that the above-mentioned problems can be solved by using an aromatic polyamide resin together with an aliphatic polyamide resin as the polyamide resin, further blending an amorphous resin, and blending a large amount of carbon black. Specifically, the above problems were solved by the following means. <1> The composition comprises a polyamide resin (A) containing an aromatic polyamide resin (A1) and an aliphatic polyamide resin (A2), a reinforcing material (B), carbon black (C), an amorphous resin (D), and a release agent (E), the mass ratio of the aromatic polyamide resin (A1) to the aliphatic polyamide resin (A2) in the polyamide resin (A) is (A1) / (A2)<1; the content of carbon black (C) is 14 to 30 parts by mass based on 100 parts by mass of the polyamide resin (A); The content of the amorphous resin (D) is 11 to 30 parts by mass relative to 100 parts by mass of the polyamide resin (A). Resin composition. <2> The content of the amorphous resin (D) is 16 to 25 parts by mass based on 100 parts by mass of the polyamide resin (A). <1> The resin composition according to claim 1. <3> A test piece formed from the resin composition has a water absorption rate of less than 3.0% when treated for 120 hours under an environment of 85°C and a relative humidity of 95%. <1> or <2> The resin composition according to claim 1. <4> the aromatic polyamide resin (A1) contains a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, and 50 mol % or more of the diamine-derived structural units are derived from xylylenediamine; <1> ~ <3> 10. The resin composition according to claim 9 . <5> 50 mol % or more of the dicarboxylic acid-derived structural units in the aromatic polyamide resin (A1) are derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms. <4> The resin composition according to claim 1. <6> The aliphatic polyamide resin (A2) contains polyamide 6 and / or polyamide 66, <1> ~ <5> 10. The resin composition according to claim 9 . <7> The reinforcing material (B) comprises glass fiber and / or talc; <1> ~ <6> 10. The resin composition according to claim 9 . <8> The content of the reinforcing material (B) is 100 to 230 parts by mass relative to 100 parts by mass of the polyamide resin (A). <1> ~ <7> 10. The resin composition according to claim 9 . <9> The content of the carbon black (C) is more than 20 parts by mass and not more than 30 parts by mass relative to 100 parts by mass of the polyamide resin (A). <1> ~ <8> 10. The resin composition according to claim 9 . <10> The amorphous resin (D) contains a styrene unit in the molecule. <1> ~ <9> 10. The resin composition according to claim 9 . <11> The release agent (E) contains a higher fatty acid metal salt and / or an aliphatic carboxylic acid amide. <1> ~ <10> 10. The resin composition according to claim 9 . <12> The content of the amorphous resin (D) is 16 to 25 parts by mass based on 100 parts by mass of the polyamide resin (A), A test piece formed from the resin composition has a water absorption rate of less than 3.0% when treated for 120 hours under an environment of 85°C and a relative humidity of 95%; the aromatic polyamide resin (A1) contains diamine-derived structural units and dicarboxylic acid-derived structural units, 50 mol % or more of the diamine-derived structural units are derived from xylylenediamine, and 50 mol % or more of the dicarboxylic acid-derived structural units are derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms; the aliphatic polyamide resin (A2) comprises polyamide 6 and / or polyamide 66, The reinforcing material (B) comprises glass fiber and / or talc, The content of the reinforcing material (B) is 100 to 230 parts by mass relative to 100 parts by mass of the polyamide resin (A), the carbon black (C) is more than 20 parts by mass and not more than 30 parts by mass relative to 100 parts by mass of the polyamide resin (A); The amorphous resin (D) contains a styrene unit in the molecule, The release agent (E) contains a higher fatty acid metal salt and / or an aliphatic carboxylic acid amide. <1> ~ <11> 10. The resin composition according to claim 9 . <13> The method includes melt-kneading carbon black (C) with the amorphous resin (D) to prepare a masterbatch of carbon black, and melt-kneading the masterbatch with the polyamide resin (A), the reinforcing material (B), and the release agent (E). <1> ~ <12> 13. A method for producing the resin composition according to claim 12. <14> <1> ~ <12> 2. A pellet of the resin composition according to claim 1. <15> <1> ~ <12> 2. A molded article molded from the resin composition according to claim 1. <16> <14> A molded article formed from the pellets according to claim 1. Effect of the Invention
[0007] According to the present invention, there is provided a resin composition comprising a polyamide resin, a reinforcing material, and a release agent, and the ΔE *The water absorption rate (%) after the moist heat test is small, and the ΔE * It is now possible to provide a resin composition capable of providing a molded article having a small grain size and excellent initial appearance, as well as a method for producing the resin composition, pellets, and a molded article. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, an embodiment of the present invention (hereinafter, simply referred to as "the present embodiment") will be described in detail. Note that the present embodiment is an example for explaining the present invention, and the present invention is not limited to the present embodiment. In this specification, the use of "to" means that the numerical values before and after it are included as the lower limit and upper limit. In this specification, various physical properties and characteristic values are those at 23° C. unless otherwise specified.
[0009] If the measurement methods, etc. described in the standards shown in this specification vary from year to year, they will be based on the standards as of January 1, 2023, unless otherwise stated.
[0010] The resin composition of the present embodiment comprises a polyamide resin (A) containing an aromatic polyamide resin (A1) and an aliphatic polyamide resin (A2), a reinforcing material (B), carbon black (C), an amorphous resin (D), and a release agent (E), and is characterized in that the mass ratio of the aromatic polyamide resin (A1) to the aliphatic polyamide resin (A2) in the polyamide resin (A) is (A1) / (A2)<1, the content of the carbon black (C) is 14 to 30 parts by mass per 100 parts by mass of the polyamide resin (A), and the content of the amorphous resin (D) is 11 to 30 parts by mass per 100 parts by mass of the polyamide resin (A). By adopting such a configuration, the resin composition containing the polyamide resin, the reinforcing material, and the release agent has a ΔE * The water absorption rate (%) after the moist heat test is small, and the ΔE * It is therefore possible to provide a resin composition capable of providing a molded product having a small grain size and excellent initial appearance.
[0011] <Polyamide resin (A)> The resin composition of the present embodiment contains an aromatic polyamide resin (A1) and an aliphatic polyamide resin (A2). Furthermore, the mass ratio of the aromatic polyamide resin (A1) to the aliphatic polyamide resin (A2) in the polyamide resin (A) is (A1) / (A2)<1. By adopting such a constitution, the strength, rigidity, and toughness of the obtained molded article tend to be improved overall. In the polyamide resin (A), the total of the aromatic polyamide resin (A1) and the aliphatic polyamide resin (A2) is usually 99% by mass or more, and may be 100% by mass.
[0012] <<Aromatic polyamide resin (A1)>> The aromatic polyamide resin (A1) in this embodiment includes a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, and 20 to 80 mol % (preferably 30 to 80 mol %, more preferably 40 to 70 mol %) of the total structural units of the diamine-derived structural unit and the dicarboxylic acid-derived structural unit are structural units containing an aromatic ring. By using such a semi-aromatic polyamide resin, the mechanical strength of the obtained molded product can be increased. Examples of semi-aromatic polyamide resins include terephthalic acid-based polyamide resins (polyamide 6T, polyamide 9T, polyamide 10T) and xylylenediamine-based polyamide resins described later, and xylylenediamine-based polyamide resins are preferred.
[0013] The resin composition of the present embodiment contains a xylylenediamine-based polyamide resin. The xylylenediamine-based polyamide resin is a polyamide resin that contains a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, and 50 mol % or more of the diamine-derived structural unit is derived from xylylenediamine. Preferably, the xylylenediamine-based polyamide resin is such that 50 mol % or more of the dicarboxylic acid-derived structural unit is derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms. In the resin composition of the present embodiment, the strength and chemical resistance inherent to the xylylenediamine-based polyamide resin can be maintained. The diamine-derived constitutional units of the xylylenediamine-based polyamide resin are preferably 60 mol% or more, more preferably 70 mol% or more, even more preferably 80 mol% or more, even more preferably 90 mol% or more, still more preferably 95 mol% or more, and particularly preferably 99 mol% or more derived from xylylenediamine (preferably paraxylylenediamine and / or metaxylylenediamine, more preferably metaxylylenediamine). The dicarboxylic acid-derived constitutional units of the xylylenediamine-based polyamide resin are preferably 60 mol% or more, more preferably 70 mol% or more, even more preferably 80 mol% or more, even more preferably 90 mol% or more, still more preferably 95 mol% or more, and particularly preferably 99 mol% or more derived from α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms.
[0014] In this embodiment, the molar ratio of metaxylylenediamine to paraxylylenediamine in the xylylenediamine, when the total of metaxylylenediamine and paraxylylenediamine is 100 moles, is preferably metaxylylenediamine / paraxylylenediamine, 10 to 100 / 90 to 0, more preferably 20 to 100 / 80 to 0, even more preferably 40 to 100 / 60 to 0, even more preferably 80 to 100 / 20 to 0, and even more preferably 90 to 100 / 10 to 0. By adopting such a configuration, the surface appearance of the obtained molded article tends to be better.
[0015] Diamines other than metaxylylenediamine and paraxylylenediamine that can be used as the raw diamine component of the xylylenediamine-based polyamide resin include aliphatic diamines such as tetramethylenediamine, pentamethylenediamine, 2-methylpentanediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, dodecamethylenediamine, 2,2,4-trimethylhexamethylenediamine, and 2,4,4-trimethylhexamethylenediamine, 1,3-bis( Examples of the diamines include alicyclic diamines such as bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, 1,3-diaminocyclohexane, 1,4-diaminocyclohexane, bis(4-aminocyclohexyl)methane, 2,2-bis(4-aminocyclohexyl)propane, bis(aminomethyl)decalin, and bis(aminomethyl)tricyclodecane; and diamines having an aromatic ring such as bis(4-aminophenyl)ether, paraphenylenediamine, and bis(aminomethyl)naphthalene. These can be used alone or in combination of two or more.
[0016] In the xylylenediamine-based polyamide resin, 50 mol % or more of the dicarboxylic acid-derived structural units are preferably derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms. The α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms preferably has 6 or more carbon atoms, and preferably has 18 or less, more preferably has 16 or less, even more preferably has 14 or less, still more preferably has 13 or less, and even more preferably has 12 or less. Examples of α,ω-linear aliphatic dicarboxylic acids having 4 to 20 carbon atoms that are suitable for use as the raw dicarboxylic acid component of the xylylenediamine-based polyamide resin include aliphatic dicarboxylic acids such as succinic acid, glutaric acid, pimelic acid, suberic acid, azelaic acid, adipic acid, sebacic acid, undecanedioic acid, and dodecanedioic acid. One or a mixture of two or more of these can be used. Among these, one or more of adipic acid, sebacic acid, and dodecanedioic acid are more preferred, and adipic acid is even more preferred. A preferred embodiment of the xylylenediamine-based polyamide resin in this embodiment is one in which 50 mol % or more (preferably 70 mol % or more, more preferably 90 mol % or more) of the dicarboxylic acid-derived structural units are derived from one or more of adipic acid, sebacic acid, and dodecanedioic acid (preferably adipic acid).
[0017] Examples of dicarboxylic acid components other than the above-mentioned α,ω-linear aliphatic dicarboxylic acids having 4 to 20 carbon atoms include phthalic acid compounds such as isophthalic acid, terephthalic acid, and orthophthalic acid, and isomers of naphthalenedicarboxylic acids such as 1,2-naphthalenedicarboxylic acid, 1,3-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 1,6-naphthalenedicarboxylic acid, 1,7-naphthalenedicarboxylic acid, 1,8-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, and 2,7-naphthalenedicarboxylic acid. These can be used alone or in combination of two or more kinds.
[0018] Incidentally, the aromatic polyamide resin (A1) contains a diamine-derived structural unit and a dicarboxylic acid-derived structural unit as main components, but does not completely exclude other structural units, and may contain lactams such as ε-caprolactam and laurolactam, and aliphatic aminocarboxylic acid-derived structural units such as aminocaproic acid and aminoundecanoic acid. Here, the main component means that, among the structural units constituting the aromatic polyamide resin (A1), the total number of the diamine-derived structural units and the dicarboxylic acid-derived structural units is the largest among all the structural units. In this embodiment, the total of the diamine-derived structural units and the dicarboxylic acid-derived structural units in the aromatic polyamide resin (A1) preferably accounts for 90% by mass or more of all the structural units, more preferably accounts for 95% by mass or more, even more preferably accounts for 97% by mass or more, and even more preferably accounts for 99% by mass or more.
[0019] The aromatic polyamide resin (A1) is preferably a crystalline resin, and its melting point is preferably 150 to 350° C., more preferably 180 to 330° C., even more preferably 200 to 330° C., and still more preferably 200 to 320° C. When the resin composition of the present embodiment contains two or more types of aromatic polyamide resins (A1), the melting point is that of the aromatic polyamide resin (A1) contained in the largest amount.
[0020] In this specification, the melting point (Tm) is a value measured by differential scanning calorimetry (DSC) in accordance with ISO11357. A differential scanning calorimeter is used, and the resin is placed in the measurement pan of the differential scanning calorimeter, heated to a temperature above the melting point at a heating rate of 10°C / min under a nitrogen atmosphere, and then rapidly cooled before measurement. The measurement conditions are a heating rate of 10°C / min, held at 280°C for 5 minutes, and then cooled down to 100°C at a cooling rate of -5°C / min to determine the melting point (Tm). As the differential scanning calorimeter, a "DSC-60" manufactured by SHIMADZU CORPORATION is used.
[0021] The aromatic polyamide resin (A1) has a number average molecular weight (Mn) of preferably 6,000 or more, more preferably 8,000 or more, and even more preferably 10,000 or more, and preferably 10,000 or less, more preferably 50,000 or less. When the resin composition of the present embodiment contains two or more kinds of aromatic polyamide resins (A1), the number average molecular weight is the number average molecular weight of the mixture.
[0022] The number average molecular weight (Mn) of the aromatic polyamide resin (A1) is measured by gel permeation chromatography (GPC) using a standard polymethyl methacrylate (PMMA) equivalent value. Two columns packed with styrene polymers are used as the packing material, and hexafluoroisopropanol (HFIP) with a sodium trifluoroacetate concentration of 2 mmol / L is used as the solvent. The resin concentration is 0.02 mass%, the column temperature is 40°C, the flow rate is 0.3 mL / min, and the measurement is performed using a refractive index detector (RI). In addition, the calibration curve is measured by dissolving six levels of PMMA in HFIP.
[0023] <<Aliphatic polyamide resin (A2)>> The resin composition of the present embodiment contains an aliphatic polyamide resin. The aliphatic polyamide resin means a polyamide resin in which aromatic monomer-derived structural units account for less than 20 mol% of all structural units in the total structural units constituting the polyamide resin. Examples of the aliphatic polyamide resin (A2) include polyamide 4, polyamide 46, polyamide 6, polyamide 66, polyamide 666, polyamide 610, polyamide 11, polyamide 116, polyamide 12, etc., and it is preferable to contain at least one of polyamide 6, polyamide 66, and polyamide 666, and it is more preferable to contain polyamide 6 and / or polyamide 66. The aliphatic polyamide resins exemplified above may contain aliphatic polyamide resins modified with other monomer units (aliphatic diamines, aromatic diamines, aliphatic dicarboxylic acids, aromatic dicarboxylic acids, aliphatic aminocarboxylic acids, aromatic aminocarboxylic acids, lactams) in a range of less than 20 mol % (preferably less than 10 mol %, more preferably less than 5 mol %, and even more preferably less than 1 mol %) of the constituent units.
[0024] <Blend ratio of polyamide resin (A)> In the resin composition of the present embodiment, the mass ratio of the aromatic polyamide resin (A1) and the aliphatic polyamide resin (A2) in the polyamide resin (A) is (A1) / (A2)<1, preferably (A1) / (A2)<0.95, more preferably (A1) / (A2)<0.90 or less, even more preferably (A1) / (A2)<0.85 or less, and preferably 0.1<(A1) / (A2), more preferably 0.2<(A1) / (A2), even more preferably 0.3<(A1) / (A2), even more preferably 0.4<(A1) / (A2), and may be 0.5<(A1) / (A2). By making (A1) / (A2)<1, it is possible to improve the toughness while maintaining the strength and rigidity of the molded article obtained. Also, by making it 0.1<(A1) / (A2), it is possible to improve the initial appearance of the molded article.
[0025] The total amount of the polyamide resin (A) in the resin composition of this embodiment is preferably 15% by mass or more, more preferably 20% by mass or more, and even more preferably 25% by mass or more in the resin composition. The upper limit of the total amount of the polyamide resin (A) in the resin composition of this embodiment is preferably 55% by mass or less, more preferably 50% by mass or less, and may be 45% by mass or less in the resin composition. The resin composition of the present embodiment may contain only one type of aromatic polyamide resin (A1) and / or two or more types of aliphatic polyamide resin (B2). When two or more types of aromatic polyamide resin (A1) and / or aliphatic polyamide resin (B2) are contained, the total amount of each is preferably within the above range.
[0026] <Reinforcement material (B)> The resin composition of the present embodiment may contain a reinforcing material (B). By containing the reinforcing material (B), the mechanical strength of the obtained molded article can be improved. The reinforcing material (B) that can be used in this embodiment is not particularly limited in terms of type, and may be any of fibers, fillers, beads, granules, whiskers, etc., with fibers and granules being preferred.
[0027] When the reinforcing material (B) is a fiber, it may be a short fiber or a long fiber. When the reinforcing material (B) is short fibers, fillers, beads, whiskers, or the like, examples of the resin composition of this embodiment include pellets, powdered versions of the pellets, and films formed from the pellets.
[0028] Examples of the raw material for the reinforcing material (B) include glass, carbon (carbon fiber, etc.), alumina, boron, ceramic, metal (steel, etc.), talc, boron nitride, mica, kaolin, barium sulfate, silicon nitride molybdenum disulfide, plants (including kenaf, bamboo, etc.), aramid, polyoxymethylene, polyparaphenylenebenzobisoxazole, ultra-high molecular weight polyethylene, and calcium carbonate include synthetic calcium carbonate, natural calcium carbonate, and surface-treated calcium carbonate obtained by surface-treating these with silicic acid or the like or an organic acid or the like, and it is preferable for the material to contain glass fiber and / or talc.
[0029] The resin composition of the present embodiment preferably contains glass fibers as the reinforcing material (B). The glass fibers are selected from glass compositions such as A-glass, C-glass, E-glass, R-glass, D-glass, M-glass, and S-glass, and E-glass (alkali-free glass) is particularly preferred. Glass fiber refers to a fibrous material whose cross section cut perpendicularly to the length direction is circular or polygonal. The number average fiber diameter of the single fiber of the glass fiber is usually 1 to 25 μm, preferably 5 to 17 μm. By making the number average fiber diameter 1 μm or more, the molding processability of the resin composition tends to be improved. By making the number average fiber diameter 25 μm or less, the appearance of the obtained molded product tends to be improved, and the reinforcing effect also tends to be improved. The glass fiber may be a single fiber or a plurality of single fibers twisted together. The form of the glass fiber may be any of glass rovings obtained by continuously winding single fibers or multiple twisted fibers, chopped strands cut to a length of 1 to 10 mm (i.e., glass fibers having a number average fiber length of 1 to 10 mm), milled fibers pulverized to a length of about 10 to 500 μm (i.e., glass fibers having a number average fiber length of 10 to 500 μm), etc., but chopped strands cut to a length of 1 to 10 mm are preferred. Glass fibers of different forms can also be used in combination. Glass fibers having an irregular cross-sectional shape are also preferred. The irregular cross-sectional shape has an aspect ratio, which is the long axis / short axis ratio of a cross section perpendicular to the longitudinal direction of the fiber, of, for example, 1.5 to 10, preferably 2.5 to 10, more preferably 2.5 to 8, and even more preferably 2.5 to 5.
[0030] The glass fiber may be surface-treated with, for example, a silane-based compound, an epoxy-based compound, a urethane-based compound, or the like, or may be oxidized, in order to improve its affinity with the resin component, as long as the properties of the resin composition of this embodiment are not significantly impaired.
[0031] The resin composition of the present embodiment preferably contains 100 parts by mass or more of the reinforcing material (B) (preferably glass fiber and / or talc) relative to 100 parts by mass of the polyamide resin (A), more preferably 130 parts by mass or more, even more preferably 135 parts by mass or more, and even more preferably 140 parts by mass or more. By making it equal to or more than the lower limit, the mechanical strength of the obtained molded body tends to be further increased. In addition, the content of the reinforcing material (preferably glass fiber and / or talc) is preferably 230 parts by mass or less, more preferably 200 parts by mass or less, and even more preferably 195 parts by mass or less relative to 100 parts by mass of the polyamide resin (A), and may be 190 parts by mass or less, 180 parts by mass or less, or 170 parts by mass or less depending on the application. By making it equal to or less than the upper limit, the appearance of the molded body tends to be improved and the moist heat resistance tends to be further improved.
[0032] The content of the reinforcing material (B) (preferably glass fiber and / or talc) in the resin composition of this embodiment is preferably 20% by mass or more, more preferably 40% by mass or more, even more preferably 45% by mass or more, and even more preferably 47% by mass or more in the resin composition. The content of the reinforcing material (preferably glass fiber and / or talc) in the resin composition is more preferably 70% by mass or less, even more preferably 65% by mass or less, even more preferably 60% by mass or less, and even more preferably 57% by mass or less. By making it equal to or more than the lower limit, the mechanical strength tends to be further increased. By making it equal to or less than the upper limit, the appearance of the molded product tends to be improved, and the flowability of the resin composition tends to be further improved. The resin composition of the present embodiment may contain only one type of reinforcing material (B), or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.
[0033] In the resin composition of this embodiment, the total content of the polyamide resin (A) and the reinforcing material (B) is preferably 65% by mass or more and 90% by mass or less in 100% by mass of the resin composition. The resin composition of the present embodiment may contain mica, but may not contain mica. An example of the resin composition of the present embodiment is one that is substantially free of mica. The term "substantially free of mica" means that the content of mica is less than 1% by mass of the total amount of the reinforcing material (B) contained in the resin composition, preferably less than 0.5% by mass, and more preferably less than 0.1% by mass. Furthermore, the resin composition of the present embodiment preferably does not substantially contain any minerals other than talc. "Substantially does not contain any minerals other than talc" means that the content of minerals other than talc is less than 1 mass%, preferably less than 0.5 mass%, and more preferably less than 0.1 mass%, of the total amount of reinforcing material (B) contained in the resin composition.
[0034] <Carbon black (C)> The resin composition of the present embodiment contains carbon black (C). By containing carbon black (C), the design of the obtained molded article can be improved and the water absorption rate of the obtained molded article can be reduced. As a result, even when the obtained molded article is placed in a humid and hot environment, the water absorption rate is reduced, and low molecular weight components in the molded article are less likely to precipitate on the surface.
[0035] As the carbon black (C) used in the present embodiment, any conventionally known carbon black can be used. Examples include furnace black, channel black, ketjen black, acetylene black, etc. Among them, carbon black with DBP absorption of 30 to 300 g / 100 cm3, which has excellent hiding power, is preferably used. 3 The use of carbon black, particularly furnace black, is preferred because it allows a stable color tone to be expressed.
[0036] In the resin composition of this embodiment, the carbon black (C) is preferably blended as a master batch of the amorphous resin (D). The concentration of the carbon black (C) in the master batch is preferably 10% by mass or more, more preferably 20% by mass or more, even more preferably 30% by mass or more, even more preferably 35% by mass or more, even more preferably 40% by mass or more, and is preferably 80% by mass or less, more preferably 70% by mass or less, even more preferably 60% by mass or less, and may be 55% by mass or less.
[0037] The content of carbon black (C) in the resin composition of the present embodiment is 14 parts by mass or more, preferably more than 20 parts by mass, and preferably 30 parts by mass or less, more preferably 28 parts by mass or less, based on 100 parts by mass of polyamide resin (A). By making it equal to or less than the upper limit, higher mechanical properties tend to be obtained. The resin composition of the present embodiment may contain only one type of carbon black (C), or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range. The content of carbon black (C) does not include the amount of resin used in the master batch.
[0038] <Amorphous resin (D)> The resin composition of the present embodiment contains an amorphous resin (D). By containing the amorphous resin (D), it is possible to further improve the moist heat property. When the polyamide resin (A) is an amorphous resin (D), the resin is classified as an amorphous resin (D). Amorphous resin (D) is a resin that does not have a clear melting point and is a polyamide resin with a crystalline fusion enthalpy ΔHm of 5 J / g or less. The crystalline fusion enthalpy (ΔHm) is measured according to differential scanning calorimetry (DSC) in accordance with ISO11357. The amorphous resin (D) is usually a thermoplastic resin.
[0039] Examples of the amorphous resin (D) include resins containing a styrene unit in the molecule, vinyl resins, PMMA resins, polycarbonate resins, modified polyphenylene ether resins, polyetherimide resins, polyamideimide resins, etc., and resins containing a styrene unit in the molecule are preferred. Examples of resins containing styrene units in the molecule include resins containing styrene units derived from styrene, α-methylstyrene, o-methylstyrene, p-methylstyrene, vinylxylene, ethylstyrene, dimethylstyrene, p-tert-butylstyrene, vinylnaphthalene, methoxystyrene, monobromostyrene, dibromostyrene, fluorostyrene, tribromostyrene, etc., and resins in which the styrene units account for 30 to 100 mass% of all constituent units are preferred. More specifically, resins containing styrene units in the molecule are preferably polystyrene resin (PS resin), acrylonitrile-butadiene-styrene resin (ABS resin), and acrylonitrile-styrene resin (AS resin), more preferably polystyrene resin (PS resin) and acrylonitrile-styrene resin (AS resin), and even more preferably acrylonitrile-styrene resin (AS resin). By using acrylonitrile-styrene resin (AS resin), the resin composition is less likely to absorb water, the amorphous portion is more easily restrained, and low molecular weight components in the resin composition are less likely to precipitate on the surface, which tends to further improve moist heat resistance.
[0040] The content of the amorphous resin (D) in the resin composition of this embodiment is 11 parts by mass or more, preferably 12 parts by mass or more, more preferably 13 parts by mass or more, even more preferably 16 parts by mass or more, and even more preferably 20 parts by mass or more, relative to 100 parts by mass of the polyamide resin (A). By making it equal to or more than the lower limit, the moist heat resistance tends to be further improved. In addition, the upper limit of the content of the amorphous resin (D) is 30 parts by mass or less, preferably 28 parts by mass or less, more preferably 26 parts by mass or less, and even more preferably 25 parts by mass or less, relative to 100 parts by mass of the polyamide resin (A). By making it equal to or less than the upper limit, the molded product formed from the resin composition tends to maintain high physical properties and have a good appearance. The resin composition of the present embodiment may contain only one type of amorphous resin (D), or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.
[0041] <Release agent (E)> The resin composition of the present embodiment contains a mold release agent (E). By containing the mold release agent (E), the releasability of the obtained molded article can be improved. The release agent (E) is mainly used to improve the productivity during molding of the resin composition. Examples of the release agent (E) include aliphatic carboxylic acid amides, aliphatic carboxylic acids, esters of aliphatic carboxylic acids and alcohols, aliphatic hydrocarbon compounds having a number average molecular weight of 200 to 15000, polysiloxane-based silicone oils, and higher fatty acid metal salts. Higher fatty acid metal salts and / or aliphatic carboxylic acid amides are preferred, and aliphatic carboxylic acid amides are more preferred.
[0042] Examples of the aliphatic carboxylic acid amide include compounds obtained by a dehydration reaction between a higher aliphatic monocarboxylic acid and / or a polybasic acid and a diamine.
[0043] As the higher aliphatic monocarboxylic acid, saturated aliphatic monocarboxylic acids and hydroxycarboxylic acids having 16 or more carbon atoms are preferred, and examples thereof include palmitic acid, stearic acid, behenic acid, montanic acid, and 12-hydroxystearic acid.
[0044] Examples of polybasic acids include aliphatic dicarboxylic acids such as malonic acid, succinic acid, adipic acid, sebacic acid, pimelic acid, and azelaic acid; aromatic dicarboxylic acids such as phthalic acid and terephthalic acid; and alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid and cyclohexylsuccinic acid.
[0045] Examples of diamines include ethylenediamine, 1,3-diaminopropane, 1,4-diaminobutane, hexamethylenediamine, metaxylylenediamine, tolylenediamine, paraxylylenediamine, phenylenediamine, and isophoronediamine.
[0046] As the aliphatic carboxylic acid amide, a compound obtained by polycondensation of stearic acid, sebacic acid, and ethylenediamine is preferred, and a compound obtained by polycondensation of 2 moles of stearic acid, 1 mole of sebacic acid, and 2 moles of ethylenediamine is more preferred. In addition to bisamide compounds obtained by reacting diamines with aliphatic carboxylic acids, such as N,N'-methylenebisstearamide and N,N'-ethylenebisstearamide, dicarboxylic acid amide compounds, such as N,N'-dioctadecylterephthalamide, can also be suitably used. In this embodiment, a release agent containing an ethylene bis stearamide structure is preferred.
[0047] Examples of the aliphatic carboxylic acid include saturated or unsaturated aliphatic mono-, di- or tri-carboxylic acids. Here, the aliphatic carboxylic acid also includes alicyclic carboxylic acids. Among these, preferred aliphatic carboxylic acids are mono- or di-carboxylic acids having 6 to 36 carbon atoms, and more preferred are saturated aliphatic mono-carboxylic acids having 6 to 36 carbon atoms. Specific examples of such aliphatic carboxylic acids include palmitic acid, stearic acid, caproic acid, capric acid, lauric acid, arachic acid, behenic acid, lignoceric acid, cerotic acid, melissic acid, tetralinic acid, montanic acid, adipic acid, and azelaic acid.
[0048] In the ester of an aliphatic carboxylic acid and an alcohol, the aliphatic carboxylic acid may be the same as the aliphatic carboxylic acid. On the other hand, the alcohol may be, for example, a saturated or unsaturated monohydric or polyhydric alcohol. These alcohols may have a substituent such as a fluorine atom or an aryl group. Among these, a monohydric or polyhydric saturated alcohol having 30 or less carbon atoms is preferred, and an aliphatic or alicyclic saturated monohydric alcohol or an aliphatic saturated polyhydric alcohol having 30 or less carbon atoms is more preferred.
[0049] Specific examples of such alcohols include octanol, decanol, dodecanol, stearyl alcohol, behenyl alcohol, ethylene glycol, diethylene glycol, glycerin, pentaerythritol, 2,2-dihydroxyperfluoropropanol, neopentylene glycol, ditrimethylolpropane, and dipentaerythritol.
[0050] Specific examples of esters of aliphatic carboxylic acids and alcohols include beeswax (a mixture mainly composed of myricyl palmitate), stearyl stearate, behenyl behenate, stearyl behenate, glycerin monopalmitate, glycerin monostearate, glycerin distearate, glycerin tristearate, pentaerythritol monopalmitate, pentaerythritol monostearate, pentaerythritol distearate, pentaerythritol tristearate, and pentaerythritol tetrastearate.
[0051] Examples of the aliphatic hydrocarbons having a number average molecular weight of 200 to 15,000 include liquid paraffin, paraffin wax, microwax, polyethylene wax, Fischer-Tropsch wax, and α-olefin oligomers having 3 to 12 carbon atoms. The aliphatic hydrocarbons herein also include alicyclic hydrocarbons. The number average molecular weight of the aliphatic hydrocarbons is preferably 5,000 or less.
[0052] The fatty acid constituting the fatty acid metal salt is preferably a fatty acid having 20 or more carbon atoms, more preferably a fatty acid having 20 to 35 carbon atoms, and even more preferably a fatty acid having 25 to 30 carbon atoms. Specific examples of the fatty acid constituting the fatty acid metal salt include stearic acid, 12-hydroxystearic acid, behenic acid, montanic acid, and ricinoleic acid. In addition, examples of the metal constituting the fatty acid metal salt include calcium, magnesium, zinc, aluminum, barium, and lithium, with calcium and barium being preferred, and barium being more preferred.
[0053] For details of the release agent, in addition to the above, the descriptions in paragraphs 0037 to 0042 of JP 2016-196563 A, the descriptions in paragraphs 0067 to 0070 of JP 2021-161125 A, and the descriptions in paragraphs 0048 to 0058 of JP 2016-078318 A can be referred to, the contents of which are incorporated herein by reference.
[0054] The content of the mold release agent (E) is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and the upper limit is preferably 1% by mass or less, more preferably 0.8% by mass or less, and even more preferably 0.5% by mass or less, based on 100% by mass of the resin composition. By setting the content within such a range, the mold releasability can be improved when performing mold molding such as injection molding, and mold contamination can be effectively suppressed. The release agent (E) may be used alone or in combination of two or more. When two or more types are used, the total amount is preferably within the above range.
[0055] <Other additives> The resin composition of the present embodiment may contain additives other than those described above (other additives). Examples of other additives include stabilizers, alkalis, hydrolysis resistance improvers, matting agents, plasticizers, dispersants, antistatic agents, coloring inhibitors, antigelling agents, etc. For details of these, please refer to the descriptions in paragraphs 0130 to 0155 of Japanese Patent No. 4894982 and the descriptions in paragraphs 0047 to 0103 of International Publication No. 2021 / 241471, the contents of which are incorporated herein by reference. The total amount of the other additives is preferably 20.0 mass % or less of the resin composition, more preferably 10.0 mass % or less, even more preferably 5.0 mass % or less, and even more preferably 1.0 mass % or less. Only one type of the other additives may be used, or two or more types may be used in combination.
[0056] <Characteristics of resin composition> The resin composition of the present embodiment is characterized in that the ΔE * Specifically, an accelerated weather resistance test was performed using an accelerated weather resistance tester (Sunshine Weather Meter) under test conditions of a black panel temperature of 63°C and water spraying for 12 minutes out of 60 minutes. * is preferably 2.6 or less, more preferably 2.5 or less, and even more preferably 2.2 or less. In addition, ΔE *The lower limit value is preferably 0, and practically 0.1 or more.
[0057] The resin composition of the present embodiment has a ΔE * Specifically, a test piece formed from the resin composition was treated in an environment of 85° C. / 95% RH for 120 hours, and the ΔE * is preferably less than 3.0, more preferably 2.5 or less, and even more preferably 2.0 or less. * The lower limit value is preferably 0, and practically 0.1 or more.
[0058] The resin composition of the present embodiment preferably has a low water absorption rate after a wet heat test. Specifically, when a test piece formed from the resin composition is treated for 120 hours under an environment of 85°C and relative humidity of 95%, the water absorption rate (mass change rate) is preferably less than 3.0%, more preferably 2.9% or less, even more preferably less than 2.8%, and even more preferably 2.7% or less. The lower limit of the water absorption rate after the wet heat test is preferably 0%, and practically 0.1% or more.
[0059] The resin composition of the present embodiment, when molded into an ISO multipurpose test piece (4 mm thick) in accordance with ISO179-1 and 2, has a notched Charpy impact strength of 10 kJ / m or less under an environment of a temperature of 23° C. and a humidity of 50%. 2 It is preferable that the concentration is 13 kJ / m or more. 2 The upper limit is not particularly specified, but is preferably 40 kJ / m 2 The following is practical. ΔE before and after accelerated weathering test * , ΔE before and after damp heat test * The water absorption rate and the Charpy impact strength before and after the wet heat test are measured according to the description in the Examples section described later.
[0060] <Method of producing resin composition> In the present embodiment, the method for producing the resin composition is not particularly specified, and a wide variety of known methods for producing thermoplastic resin compositions can be used. Specifically, the resin composition can be produced by mixing the components in advance using various mixers such as a tumbler or a Henschel mixer, and then melt-kneading the components using a Banbury mixer, a roll, a Brabender, a single-screw extruder, a twin-screw extruder, a kneader, or the like.
[0061] Also, for example, the resin composition can be produced by not mixing the components in advance, or by mixing only some of the components in advance, feeding the mixture to an extruder using a feeder, and melt-kneading the mixture. Furthermore, for example, some of the components (such as colorants) can be mixed in advance, fed into an extruder, and melt-kneaded to obtain a masterbatch composition, which can then be mixed again with the remaining components and melt-kneaded to produce pellets. In particular, the resin composition of the present embodiment is preferably produced by a production method including: producing a masterbatch of carbon black by melt-kneading carbon black (C) with an amorphous resin (D); and melt-kneading the masterbatch with the polyamide resin (A), the reinforcing material (B), and the release agent (E).
[0062] <Molded products> The molded article of the present embodiment is formed from the resin composition or pellets of the present embodiment. The method for producing the molded article of the present embodiment is not particularly limited. As an example, an injection molded article molded by injection molding is exemplified. For example, the molded product of this embodiment may be produced by melt-kneading the components and then directly molding the components using various molding methods, or by melt-kneading the components and pelletizing them, and then melting them again and molding them using various molding methods.
[0063] The method for molding the molded product is not particularly limited, and any conventionally known molding method can be used, such as injection molding, injection compression molding, extrusion molding, profile extrusion, transfer molding, hollow molding, gas-assisted hollow molding, blow molding, extrusion blow molding, IMC (in-mold coating molding), rotational molding, multi-layer molding, two-color molding, insert molding, sandwich molding, foam molding, and pressure molding.
[0064] The shape of the molded product of the present embodiment is not particularly limited and can be appropriately selected depending on the application and purpose of the molded product. Examples of the shape include plate-like, plate-like, rod-like, sheet-like, film-like, cylindrical, annular, circular, elliptical, gear-like, polygonal, irregularly shaped, hollow, frame-like, box-like, and panel-like shapes.
[0065] The application field of the molded product of this embodiment is not particularly limited, and it is widely used in automobile and other transportation machinery parts, general machine parts, precision machine parts, electronic and electrical equipment parts, office automation equipment parts, building materials and housing related parts, medical devices, leisure sports goods, play equipment, medical products, daily necessities such as food packaging films, defense and aerospace products, etc. EXAMPLES
[0066] The present invention will be described in more detail below with reference to examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below. If the measuring instruments used in the examples are difficult to obtain due to discontinuation or the like, measurements can be made using other instruments with equivalent performance.
[0067] 1.Raw materials The raw materials shown in Table 1 below were used. [Table 1]
[0068] <Production Example 1: Masterbatch (1)> Acrylonitrile-styrene resin (AS resin), carbon black, and barium stearate (mold release agent) were melt-kneaded in a ratio of AS resin / carbon black=49.5 / 50 / 0.5 (mass ratio) to obtain master batch (1). AS resin is a non-crystalline resin.
[0069] <Production Example 2: Masterbatch (2)> Polyamide 6 and carbon black were melt-kneaded in a ratio of polyamide 6 / carbon black = 75 / 25 (mass ratio) to obtain a master batch (2).
[0070] 2. Examples 1 to 4 and Comparative Examples 1 to 6 <Compound> As shown in Tables 2 and 3, each component was weighed (each component is expressed in parts by mass), and the components other than the glass fiber were blended in a tumbler, and the blend was added to the base of a twin-screw extruder (Shibaura Machine Co., Ltd., TEM26SS) and melted. The glass fiber was then side-fed to prepare pellets of the resin composition. The temperature of the twin-screw extruder was set to 280°C.
[0071] <ΔE before and after accelerated weathering test * > The pellets obtained by the above manufacturing method were dried at 120°C for 4 hours, and then flat test pieces (60mm x 60mm x 2mmt) with embossed surfaces were produced using an injection molding machine (Japan Steel Works, Ltd., "J100ADS") under conditions of a cylinder temperature of 280°C, a mold temperature of 130°C, and a molding cycle of 50 seconds. The flat test pieces were placed in an accelerated weather resistance tester (Sunshine Weather Meter) and treated for 2000 hours under test conditions of a black panel temperature of 63°C and 12 minutes of water spraying out of 60 minutes. The test pieces were removed and the L of the surface was measured using a spectrophotometer "SE6000" manufactured by Nippon Denshoku Industries Co., Ltd. * , a * , b * The measured L * , a * , b * and L on the surface of the test piece before the test * , a * , b * from ΔE *The measured ΔE * The maximum value of ΔE before and after accelerated weathering test * It was decided. The accelerated weather resistance tester (Sunshine Weather Meter) used was manufactured by Suga Test Instruments Co., Ltd.
[0072] <Water absorption rate in wet heat test (%)> The flat test piece prepared by the above method was placed in a thermo-hygrostat and treated at 85°C / 95% RH for 120 hours. The mass change rate calculated from the mass of the test piece before and after the test was taken as the water absorption rate. The thermohygrostat "PL-3KP" manufactured by Espec Corporation was used.
[0073] <ΔE before and after damp heat test * > The flat test piece placed in the thermo-hygrostat by the above method and the L of the test piece surface before the test * , a * , b * is measured using a spectrophotometer, and ΔE * was calculated. The spectrophotometer used was the "SE6000" manufactured by Nippon Denshoku Industries Co., Ltd.
[0074] <Initial appearance of textured molded product> The textured surface of the flat test piece prepared by the above method was visually inspected. The appearance was evaluated as A or B. The evaluation was performed by five experts and judged by majority vote. A: There is no appearance defect on the surface of the test piece. B: Poor appearance (precipitation of reinforcing material, gas burns) was confirmed on part of the test piece surface.
[0075] <Bending properties> The pellets obtained by the above manufacturing method were dried at 120°C for 4 hours, and then injection molded into ISO multipurpose dumbbell test pieces type A1 (4 mm thick) using an injection molding machine (Nissei Plastic Industrial Co., Ltd., "NEX140III") under conditions of a cylinder temperature of 280°C, a mold temperature of 130°C, and a molding cycle of 50 seconds. In accordance with ISO178, the bending strength (unit: MPa) and bending modulus (unit: GPa) were measured in an environment of a temperature of 23°C and a humidity of 50%.
[0076] <Charpy impact strength> The pellets obtained by the above manufacturing method were dried at 120°C for 4 hours, and then injection molded into ISO multipurpose test pieces type A1 (4 mm thick) using an injection molding machine (manufactured by Nissei Plastic Industrial Co., Ltd., "NEX140III") under conditions of a cylinder temperature of 280°C, a mold temperature of 130°C, and a molding cycle of 50 seconds. The ISO multipurpose test piece was cut to a specified size and shape, and the notched Charpy impact strength (unit: kJ / m) was measured in accordance with ISO179-1 and 2 using the above ISO multipurpose test piece (4 mm thick) at a temperature of 23°C and humidity of 50%. 2 ) was measured.
[0077] [Table 2]
[0078] [Table 3]
[0079] As is clear from the above results, the molded article formed from the resin composition of the present embodiment has a high mechanical strength and a large ΔE * The water absorption rate (%) after the moist heat test is low, and the ΔE * In particular, by making the ratio of carbon black (C) more than 20 parts by mass relative to polyamide resin (A), a remarkably excellent ΔE * and ΔE before and after the heat and humidity test * could be significantly reduced.
Claims
1. The present invention comprises a polyamide resin (A) including an aromatic polyamide resin (A1) and an aliphatic polyamide resin (A2), a reinforcing material (B), carbon black (C), an amorphous resin (D), and a release agent (E), the mass ratio of the aromatic polyamide resin (A1) to the aliphatic polyamide resin (A2) in the polyamide resin (A) is (A1) / (A2)<1; The content of carbon black (C) is 14 to 30 parts by mass based on 100 parts by mass of the polyamide resin (A), The content of the amorphous resin (D) is 11 to 30 parts by mass based on 100 parts by mass of the polyamide resin (A). Resin composition.
2. The resin composition according to claim 1, wherein the content of the amorphous resin (D) is 16 to 25 parts by mass per 100 parts by mass of the polyamide resin (A).
3. 3. The resin composition according to claim 1, wherein a test piece formed from the resin composition has a water absorption rate of less than 3.0% when treated at 85°C and a relative humidity of 95% for 120 hours.
4. The aromatic polyamide resin (A1) contains a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, and 50 mol% or more of the diamine-derived structural unit is derived from xylylenediamine. The resin composition according to claim 1 or 2.
5. The resin composition according to claim 4, wherein 50 mol% or more of the dicarboxylic acid-derived structural units in the aromatic polyamide resin (A1) are derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms.
6. The resin composition according to claim 1 or 2, wherein the aliphatic polyamide resin (A2) comprises polyamide 6 and / or polyamide 66.
7. The resin composition according to claim 1 or 2, wherein the reinforcing material (B) comprises glass fiber and / or talc.
8. The resin composition according to claim 1 or 2, wherein the content of the reinforcing material (B) is 100 to 230 parts by mass per 100 parts by mass of the polyamide resin (A).
9. The resin composition according to claim 1 or 2, wherein the content of the carbon black (C) is more than 20 parts by mass and not more than 30 parts by mass per 100 parts by mass of the polyamide resin (A).
10. The resin composition according to claim 1 or 2, wherein the amorphous resin (D) contains a styrene unit in the molecule.
11. The resin composition according to claim 1 or 2, wherein the release agent (E) comprises a metal salt of a higher fatty acid and / or an aliphatic carboxylic acid amide.
12. The content of the amorphous resin (D) is 16 to 25 parts by mass based on 100 parts by mass of the polyamide resin (A), A test piece formed from the resin composition has a water absorption rate of less than 3.0% when treated for 120 hours under an environment of 85° C. and a relative humidity of 95%; the aromatic polyamide resin (A1) contains diamine-derived structural units and dicarboxylic acid-derived structural units, 50 mol % or more of the diamine-derived structural units are derived from xylylenediamine, and 50 mol % or more of the dicarboxylic acid-derived structural units are derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms; The aliphatic polyamide resin (A2) contains polyamide 6 and / or polyamide 66, The reinforcing material (B) contains glass fiber and / or talc, The content of the reinforcing material (B) is 100 to 230 parts by mass relative to 100 parts by mass of the polyamide resin (A), the carbon black (C) is more than 20 parts by mass and not more than 30 parts by mass relative to 100 parts by mass of the polyamide resin (A); The amorphous resin (D) contains a styrene unit in a molecule, The resin composition according to claim 1 , wherein the release agent (E) comprises a metal salt of a higher fatty acid and / or an aliphatic carboxylic acid amide.
13. 13. A method for producing a resin composition according to claim 1, comprising: preparing a master batch of carbon black by melt-kneading carbon black (C) with the amorphous resin (D); and melt-kneading the master batch with the polyamide resin (A), the reinforcing material (B), and the release agent (E).
14. A pellet of the resin composition according to claim 1, 2 or 12.
15. A molded article molded from the resin composition according to claim 1, 2 or 12.
16. A molded article formed from the pellets of claim 14.
Citation Information
Patent Citations
Resin composition and molded article
JP2019143023A